A soft 3D polyacrylate hydrogel recapitulates the cartilage niche and allows growth-factor free tissue engineering of human articular cartilage. (May 2019) - Jiménez, Gema; Venkateswaran, Seshasailam; López-Ruiz, Elena; Perán, Macarena; Pernagallo, Salvatore; Díaz-Monchón, Juan J.; Canadas, Raphael F.; Antich, Cristina; Oliveira, Joaquím M.; Callanan, Anthony; Walllace, Robert; Reis, Rui L.; et al.
Graphical abstract: Abstract: Cartilage degeneration or damage treatment is still a challenge, but, tissue engineering strategies, which combine cell therapy strategies, which combine cell therapy and scaffolds, and have emerged as a promising new approach. In this regard, polyurethanes and polyacrylates polymers have been shown to have clinical potential to treat osteochondral injuries. Here, we have used polymer microarrays technology to screen 380 different polyurethanes and polyacrylates polymers. The top polymers with potential to maintain chondrocyte viability were selected, with scale-up studies performed to evaluate their ability to support chondrocyte proliferation during long-term culture, while maintaining their characteristic phenotype. Among the selected polymers, poly (methylmethacrylate-co-methacrylic acid), showed the highest level of chondrogenic potential and was used to create a 3D hydrogel. Ultrastructural morphology, microstructure and mechanical testing of this novel hydrogel revealed robust characteristics to support chondrocyte growth. Furthermore, in vitro and in vivo biological assays demonstrated that chondrocytes cultured on the hydrogel had the capacity to produce extracellular matrix similar to hyaline cartilage, as shown by increased expression of collagen type II, aggrecan and Sox9, and the reduced expression of the fibrotic marker's collagen type I. In conclusion, hydrogels generated from poly (methylmethacrylate-co-methacrylic acid) created the appropriate niche for chondrocyte growth and phenotype maintenance and might be an optimal candidate for cartilage tissue-engineering applications. Significance Statement: Articular cartilage has limited self-repair ability due to its avascular nature, therefore tissue engineering strategies have emerged as a promising new approach. Synthetic polymers displaygreat potential and are widely used in the clinical setting. In our study, using the polymer microarray technique a novel type of synthetic polyacrylate was identified, that was converted into hydrogels for articular cartilage regeneration studies. The hydrogel based on poly (methylmethacrylate-co-methacrylic acid-co-PEG-diacrylate) had a controlable ultrastructural morphology, microstructure (porosity) and mechanical properties (stiffness) appropriate for cartilage engineering. Our hydrogel created the optimal niche for chondrocyte growth and phenotype maintenance for long-term culture, producing a hyaline-like cartilage extracellular matrix. We propose that this novel polyacrylate hydrogel could be an appropriate support to help in the treatment efficient cartilage regeneration.